Surfing the net for software engineering notes. - Doernhoefer, Mark (Software engineering notes.)
Agile methods are one of the most controversial topics in the software development community today. The homepage for this year's Agile Development Conference remarked that one of the purposes of this year's conference was to dispel the notion that agile development methods are "a bunch of hot air". And indeed, the amount of hype surrounding this new approach to writing software would lead one to believe that agile methods are long on promises and short on rigor. Even some of the terms surrounding agile methods; Extreme Programming (XP), Crystal, Scrum, etc., seem like they were developed by an advertising agency instead of a software process improvement group.